Effect of glucocorticoids on the oxidative desaturation of fatty acids by rat liver microsomes. - I N de Gómez Dumm; M J de Alaniz; R R Brenner (Journal of Lipid Research, 1979)
The effect of glucocorticoids on the oxidative desaturation of fatty acids by liver microsomal preparations of rats has been studied. Hydrocortisone produced a significant decrease in the conversion of [1-14C]linoleic acid to gamma-linolenic acid and [1-14C]eicosa-8, 11, 14-trienoic acid to arachidonic acid. Triamcinolone and dexamethasaone were more active than hydrocortisone in depressing delta 6 and delta 5 fatty acid desaturating activity in liver microsomes. The glucocorticoids evoked a maximal response approximately 24 hr after admission. Palmitic acid conversion to palmitoleic acid showed no statistically significant changes by any of the glucocorticoids. The mechanism of action of glucocorticoids is apparently different from other hyperglycemic hormones that produce similar effects.